Uwarunkowania i dotychczasowe skutki inwazji Rosji na Ukrainę – (nie)bezpieczeństwo ontologiczne, przetrwanie reżimu czy dewiacja ideologiczna? - Polegkyi, Oleksii; Stępniewski, Tomasz (Studia Polityczne, 2024)
The article explains the reasons for the Russian offensive against Ukraine in terms of national security and Putin’s regime’s fear of democratization. It also offers a reflection upon ideological foundations prevalent in the Russian society. Such an approach will facilitate the understanding of how, in light of the core values and characteristics of that society, Ukraine has been portrayed as both a threat for Russian identity and an existential threat for Russia itself. The Russian invasion of Ukraine was undoubtedly aimed at gaining support at home and strengthening Putin’s regime. However, war is also integral to Putin’s project of Russia. Putin’s imperial thrust is rooted in the internal dynamics of this system. The current Russian regime is not so much based on ideology as it is striving to turn its propaganda clichés into an ideological platform. On the other hand, the war is accelerating the process of change in Russia – the current situation could lead to the collapse of Putin’s regime and even the disintegration of the Russian Federation itself, which harkens back to the collapse of the USSR.